Influence of Temperature and Sweating Duration on The Quality of Vanilla (Vanilla planifolia Andrews) - Farida Kurniasari; I Wayan Budiastra; Dyah Wulandani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Indonesia has significant potential for vanilla production. However, in terms of quality, Indonesian dried vanilla still has a low standard, one of the factors being the suboptimal post-harvest technology, particularly in the sweating process. This research aims to determine the optimal temperature and sweating duration to achieve the best vanilla quality in accordance with the Indonesian National Standard (SNI). After the harvesting process, the vanilla pods were treated by soaking them in warm water at a temperature of 65°C for 3 minutes. After the vanilla pods were wilted, they were wrapped using a combination of a towel cloth-black cloth-burlap. They were then sweated in an incubator at 40°C with 70% RH and 45°C with 70% RH for 2, 4, and 6 days. The observed vanilla quality parameters include weight loss, color, hedonic tests (aroma and color), vanillin content based on the methods of SNI 01-0010-2002 and ash content based on the methods of AOAC. The result shows that the optimal temperature and duration for sweating in an incubator are 40°C and 4 days. Keywords: Postharvest, Quality, Sweating, Vanilla, Vanillin.